Comparison of the effects of mobile technology AAC apps on programming visual scene displays. (2nd October 2017) - Caron, Jessica; Light, Janice; Davidoff, Beth E.; Drager, Kathryn D. R.
Abstract: Parents and professionals who work with individuals who use augmentative and alternative communication (AAC) face tremendous time pressures, especially when programming vocabulary in AAC technologies. System design (from programming functions to layout options) necessitates a range of skills related to operational competence and can impose intensive training demands for communication partners. In fact, some AAC applications impose considerable learning demands, which can lead to increased time to complete the same programming tasks. A within-subject design was used to investigate the comparative effects of three visual scene display AAC apps (GoTalk Now, AutisMate, EasyVSD) on the programming times for three off-line programming activities, by adults who were novices to programming AAC apps. The results indicated all participants were able to create scenes and add hotspots during off-line programming tasks with minimal self-guided training. The AAC app that had the least number of programming steps, EasyVSD, resulted in the fastest completion times across the three programming tasks. These results suggest that by simplifying the operational requirements of AAC apps the programming time is reduced, which may allow partners to better support individuals who use AAC.